Basic Psychological Need Profiles and Correlates in Physical Activity Participation: A Person-Centered Approach - Li, Chunxiao; Wang, Chee Keng John; Koh, Koon Teck; Tan, Kwang San Steven; Tan, Shern Meng; Ang, Wee Boon; Wong, Liang Han; Yeo, Huat Neo Connie (Frontiers in Psychology, 2021)
Guided by Basic Psychological Need Theory, we investigated the combined associations between need satisfaction and need frustration (i.e., need profiles), and their relations with theoretically relevant correlates including mindfulness, physical literacy, physical activity enjoyment, and physical activity. Participants were Singapore-based school students (N = 844, Mage = 12.45, SDage = 1.99, Boys = 53.1%) who completed a cross-sectional survey. The results of the latent profile analysis identified four distinct need profiles: Profile 1 “Average Satisfaction and Frustration” (n = 364, 44.1%), Profile 2 “Low Satisfaction (n = 251, 29.7%), Above Average Frustration”, Profile 3 “Very High Satisfaction, Very Low Frustration” (n = 144, 17.1%), and Profile 4 “High Satisfaction, Very High Frustration" (n = 85, 10.1%). Among which, Profile 3 was the most adaptive one, which had the highest levels of mindfulness, physical literacy, physical activity enjoyment, and moderate-to-vigorous physical activity. Experiences of need satisfaction countered the negative effects of need frustration on these correlates. These findings enhance our understanding of students’ psychological need experiences and highlight the need for investigating the combined associations between need satisfaction and need frustration.